GABAergic striatal neurons project dendrites and axons into the postnatal subventricular zone leading to calcium activity - Young, Stephanie Z.; Lafourcade, Carlos A.; Platel, Jean-claude; Lin, Tiffany; Bordey, Angelique (Frontiers in Cellular Neuroscience, 2014)
GABA regulates the behavior of neuroblasts and neural progenitor cells in the postnatal neurogenic subventricular zone (SVZ) through GABAA receptor (GABAAR)-mediated calcium increases. However, the source of GABA necessary for sufficient GABAAR-mediated depolarization and calcium increase has remained speculative. Here, we explored whether GABAergic striatal neurons functionally connect with SVZ cells. Using patch clamp recordings or single cell electroporation, striatal neurons along the SVZ were filled with a fluorescent dye revealing that they send both dendrites and axons into the SVZ. About 93% of the recorded neurons were medium spiny or aspiny GABAergic neurons and each neuron sent 3-4 processes into the SVZ covering ~56 µm. Using calcium imaging, we found that depolarization of striatal neurons led to increased calcium activity in SVZ cells that were mediated by GABAAR activation. Collectively, these findings undercover a novel mode of signaling in the SVZ providing a mechanism of brain activity-mediated regulation of postnatal neurogenesis through GABAergic striatal activity.